verify =x×(y×z) = (x×y)×z x=-4/10, y=5/64, z=32/3​

Question

verify =x×(y×z) = (x×y)×z
x=-4/10, y=5/64, z=32/3​

in progress 0
Adeline 1 month 2021-10-28T04:10:05+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-10-28T04:11:34+00:00

    Step-by-step explanation:

    x×(y×z) = (x×y)×z

    L.H.S

    = -4/10 x (5/64 x 32/3)

    = -4/10 x {(5×32) / (64x 3)}

    = -4/10 x 5/(2×3)

    = -4/10 x 5/6

    = (-4×5) / (10×6)

    = -20/60

    = -1/3

    R.H.S

    = (-4/10 x 5/64) x 32/3

    = {(-4×5)/(10×64)} x 32/3

    = ( -20/640) x 32/3

    = (-1/32) x 32/3

    = (-1×32)/(32×3)

    = -1/3

    L.H.S = R.H.S (Hence proved)

    0
    2021-10-28T04:12:00+00:00

    Answer:

    -1/3=-1/3

    Step-by-step explanation:

    step 1: x*(y*z)=(x*y)*z

    step 2: x=-4/10

    y=5/64

    z=32/3

    step 3:LHS.

    -4/10*(5/64*32/3)

    =-1/3

    step 4:RHS

    ( -4/10*5/64)*32/3

    =-1/3

    step 5: LH=RHS

    -1/3=-1/3

    HENCE PROVED.

Leave an answer

Browse

14:4+1-6*5-7*14:3+5 = ? ( )